A study of biological aspects of the krill population (Euphausia Superba Dana, 1892) at northern South Georgia Island in July-October 2001 - M. S. Savych; N. N. Zhuk (Ukrainian Antarctic Journal, 2004)
We consider the biological state of Antarctic krill Euphausia superba inhabiting the shelf and the slope at northern South Georgia Island in poorly investigated winter (July-August) and spring (September-October) months of 2001. According to the results of the research two size groups were distinguished – juveniles and mature individuals, characterized by seasonal variability of morphophysiological parameters as well as negative features – resorption of spermatophores in males and krill’s disease of soft tissues.